Nutritional supplements in sports and exercise - Greenwood, Mike (Springer, 2017)
This new text presents the most up-to-date research based information regarding popular sport/performance nutrient dense diets and nutritional supplements and their constituents that directly or indirectly utilize them. Previous chapters have been fully revised and new chapters have been added to cover important cutting edge topics. New chapters include: (1) Carbohydrate Utilization and Disposal in Strength/Power Training & Sports, (2) Exercise for Athletes with Diabetes, and (3) Beyond the Obvious: Future Innovations in Sports Nutrition. The volume is divided into four sections: (1) The Industrial Nature of the Supplement Game; (2) Nutritional Basics First; (3) Specialized Nutritional Strategies & Supplements; and (4) Present and Future Directions of Nutritional Supplements. Editors and authors are co-founders, board members or members of the International Society of Sports Nutrition and or current/former doctoral students from the Exercise and Sport Nutrition Laboratory located at Texas A&M University. Nutritional Supplements in Sports and Exercise, Second Edition presents cutting edge information and is valuable to sports nutritionists, exercise physiologists, strength and conditioning/personal trainers, athletic trainers, athletic coaches, registered dietitians, and college/professional sport affiliates.